Complete Pattern of Ocular Dominance Columns in Human Primary Visual Cortex - Adams, Daniel L; Sincich, Lawrence C; Horton, Jonathan C (The Journal of neuroscience, 2007)
The occipital lobes were obtained after death from six adult subjects with monocular visual loss. Flat-mounts were processed for cytochrome oxidase (CO) to reveal metabolic activity in the primary (V1) and secondary (V2) visual cortices. Mean V1 surface area was 2643 mm 2 (range, 1986–3477 mm 2 ). Ocular dominance columns were present in all cases, having a mean width of 863 μm. There were 78–126 column pairs along the V1 perimeter. Human column patterns were highly variable, but in at least one person they resembled a scaled-up version of macaque columns. CO patches in the upper layers were centered on ocular dominance columns in layer 4C, with one exception. In this individual, the columns in a local area resembled those present in the squirrel monkey, and no evidence was found for column/patch alignment. In every subject, the blind spot of the contralateral eye was conspicuous as an oval region without ocular dominance columns. It provided a precise landmark for delineating the central 15° of the visual field. A mean of 53.1% of striate cortex was devoted to the representation of the central 15°. This fraction was less than the proportion of striate cortex allocated to the representation of the central 15° in the macaque. Within the central 15°, each eye occupied an equal territory. Beyond this eccentricity, the contralateral eye predominated, occupying 63% of the cortex. In one subject, monocular visual loss began at age 4 months, causing shrinkage of ocular dominance columns. In V2, which had a larger surface area than V1, CO stripes were present but could not be classified as thick or thin.